Representation of the Female Body as a Substance of Contemporary Ornamentation in Metal Jewelry - Widiyanti, Dhyani (Institut Seni Indonesia Yogyakarta, 2024)
This study explores the role of surrealism in metal jewelry design as it pertains to the representation of the female body. The research focuses on the works of three contemporary metal jewelry artists from Etsy, examining how their creations utilize surrealism to express experiences of castration and fetishism, as theorized by Freud. It investigates the interplay between functionality and unconventional forms, highlighting how surrealism allows for a critique of traditional gender norms and a subversion of established visual conventions. By employing literature studies and visual analysis, the research demonstrates how these surrealist elements in metal jewelry serve as a medium for expressing complex narratives about femininity, identity, and bodily autonomy. The findings contribute to a deeper understanding of how surrealism can be a powerful tool in challenging and reinterpreting conventional representations of the female body in contemporary art.ABSTRAKPenelitian ini mengeksplorasi peran surealisme dalam desainperhiasan logam terkait dengan representasi tubuh perempuan.Penelitian ini berfokus pada karya tiga seniman perhiasan logamkontemporer dari Etsy, mengkaji bagaimana kreasi mereka menggunakansurealisme untuk mengekspresikan pengalaman kastrasi dan fetisisme,seperti yang diteorikan oleh Freud. Penelitian ini menyelidiki interaksiantara fungsionalitas dan bentuk-bentuk yang tidak lazim, menyorotibagaimana surealisme memungkinkan kritik terhadap norma-norma gender tradisional dan subversi terhadap konvensi visual yang mapan. Dengan menggunakan studi literatur dan analisis visual, penelitian ini menunjukkan bagaimana elemen-elemen surealis dalam perhiasan logam berfungsi sebagai media untuk mengekspresikan narasi kompleks tentang feminitas, identitas, dan otonomi tubuh. Temuan ini berkontribusi pada pemahaman yang lebih mendalam tentang bagaimana surealisme dapat menjadi alat yang kuat dalam menantang dan menafsirkan ulang representasi konvensional tubuh perempuan dalam seni kontemporer.